Project management theory and practice - Richardson, Gary L. (Auerbach Publications/CRC Press, 2010)
Offers students with a complete overview of project management theory - in language they can easily understand. This text integrates the organizational environment that surrounds a project to supply students with the well-rounded knowledge of theories, organizational issues, and human behavior needed to effectively manage real-world projects